POLA BAKTERI DAN USIA PASIEN TERHADAP PROKALSITONIN DI PNEUMONIA KOMUNITAS DAN NOSOKOMIAL - Coriejati Coriejati; Mohammad Iqbal; Emmy Hermyanti Pranggono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Pneumonia is one of an infectious disease with high mortality rate. In the last decade procalcitonin (PCT) was found as a biomarkerthat can predict a kind of infection. The aim of the study was to know the difference of PCT level between community acquired pneumonia(CAP) and hospital acquired pneumonia (HAP) by analyzing it, and the difference between <60 years old and older age patients. Across-sectional study was conducted on the CAP and HAP patients in RSHS, in August–October 2009. The level difference were analyzedwith Mann-Whitney test, with a significancy of p<0.05. In this study 40 (forty) patients (66%) CAP and 21 patients (34%) HAP wereincluded. The median of PCT levels in CAP was 0.88 ng/dL and HAP 8.32 ng/dL (p=0.002), where as in the in Gram negative bacterialinfection (GNBI) level in CAP was 4.76 ng/dL and in Gram positive was 0.61 ng/dL. The median PCT level in HAP with Gram negativewas 19.02 ng/dL and in the Gram positive was 4.63 ng/dL (p=0.201). The median of PCT level in CAP group <60 yo was 1.42 ng/dLand in ≥60 yo was 0.65 ng/dL (p=0.207). The median of PCT level in HAP <60 yo was 8.32 ng/dL, where as in ≥60 yo was 9.93ng/dL (p=0.178). Based in this study can be concluded that the PCT level in HAP group was higher than in the CAP group. The PCTlevel in HAP with Gram negative bacterial infection was higher than in the CAP, where as in the CAP group was lower in ≥60 yo.